2011
DOI: 10.1177/0363546511417407
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Sport-Specific Impairments After Arthroscopic Bankart Repair

Abstract: The athletes' shoulder stabilization resulted in a prolonged rehabilitation depending on the functional demand of the performed shoulder-dependent sport, as shown by the specific shoulder sport score systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 49 publications
5
114
0
1
Order By: Relevance
“…In accordance with the results of Stein et al, 33 martial arts, a high-risk activity for shoulder dislocation, was the only activity that dropped significantly in participation. Patients extending their activities to new sports most frequently chose activities with a low risk for shoulder dislocation.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with the results of Stein et al, 33 martial arts, a high-risk activity for shoulder dislocation, was the only activity that dropped significantly in participation. Patients extending their activities to new sports most frequently chose activities with a low risk for shoulder dislocation.…”
Section: Discussionsupporting
confidence: 89%
“…The underlying reason is that the risk factor was considered and patients were selected in accordance with these factors. In the literature, similar results can be seen [2,10,11].…”
Section: J Nov Physiothersupporting
confidence: 82%
“…Traumatic shoulder dislocation frequently requires surgical repair. Re-dislocation rates after non-surgical treatment in young athletes approach 90% to 100% [1,2]. The open bankart repair is gold standard.…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al 26 focused on shoulder sport-specific impairments after arthroscopic Bankart repair. The investigators concluded that sport-specific impairments are not detectable Remarkably, the investigators found differences in scores when using the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire-a score not specifically designed for shoulder instability.…”
Section: Discussionmentioning
confidence: 99%